Heterogeneous effects of marketing contracts and resource-providing contracts on household income - Ruml, Anette; Ragasa, Catherine; Qaim, Matin (Universität Göttingen, 2020)
In the existing literature, the effects of contract farming on household welfare were examined with mixed results. Most studies looked at single contract types. This paper contributes to the literature by comparing two types of contracts – simple marketing contracts and resource providing contracts – in the Ghanaian oil palm sector. We investigate the effects of both contracts on farm income, as well as spillovers on other household income sources. We use survey data collected with an innovative sampling design and a control function approach to address possible issues of endogeneity. Both contracts lead to large positive effects on total household income in a similar magnitude, yet through quite different mechanisms. Farmers under the marketing contract use the increase in oil palm profits to transition out of agricultural production and into off-farm employment. Farmers under the resource-providing contract have a stronger dependency on income from oil palm, which is considerably more profitable under the contract. The findings underline that contract characteristics matter for the effects and that disaggregated analysis of different income sources is important to understand the underlying mechanisms.